2016
DOI: 10.1093/nar/gkw826
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 localization to lineage-specific enhancers is associated with a distinct transcription factor repertoire

Abstract: Proper temporal epigenetic regulation of gene expression is essential for cell fate determination and tissue development. The Bromodomain-containing Protein-4 (BRD4) was previously shown to control the transcription of defined subsets of genes in various cell systems. In this study we examined the role of BRD4 in promoting lineage-specific gene expression and show that BRD4 is essential for osteoblast differentiation. Genome-wide analyses demonstrate that BRD4 is recruited to the transcriptional start site of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
112
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 84 publications
17
112
0
Order By: Relevance
“…These findings support previous studies which demonstrate that early tissue‐specific loss of Brd4 prevents lineage commitment of myoblasts and adipocytes (J. E. Lee et al, ). Additionally, Brd4 inhibition has been shown to prevent differentiation of human fetal osteoblasts (Najafova et al, ) and slow progression of osteosarcoma cells (Lamoureux et al, ). Our findings corroborate these previous observations in MC3T3 osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support previous studies which demonstrate that early tissue‐specific loss of Brd4 prevents lineage commitment of myoblasts and adipocytes (J. E. Lee et al, ). Additionally, Brd4 inhibition has been shown to prevent differentiation of human fetal osteoblasts (Najafova et al, ) and slow progression of osteosarcoma cells (Lamoureux et al, ). Our findings corroborate these previous observations in MC3T3 osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…This family of epigenetic reader proteins provides a plausible link between histone modifications and subsequent activation of the osteoblastic transcriptional network. Indeed, prior studies have suggested that Brd4 may contribute to biological regulation of osteogenesis (Baud'huin et al, ; Najafova et al, ). In the current study, we evaluated the expression levels of a large panel of BRD proteins ( n = 40), including multiple BET proteins ( n = 7) in MC3T3 osteoblasts and assessed the impact of Brd2 and Brd4 loss of function by small interfering RNA (siRNA)‐mediated knock‐down and small molecule inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies highlight the central role of BRD4 in enhancer activity (69,26). This study reveals a specific association of BRD4 with distal regions of basal epithelial-specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…BRD4 is a central regulator of lineage- and tumor-specific transcriptional progams and functions to increase transcriptional activity by binding to acetylated lysine residues at distal and proximal regulatory regions (30,34,35). CHD1-dependent genes showed a high occupancy of CHD1 which extended into the gene body, while displaying comparatively low RNAPII occupancy around the TSS (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%